1988
DOI: 10.1002/ajmg.1320290124
|View full text |Cite
|
Sign up to set email alerts
|

Duplication 11q and deletion 5p syndromes due to a reciprocal translocation segregating in four generations

Abstract: We report on 2 relatives with duplication 11q and deletion 5p, resulting from an adjacent-1 segregation of a balanced reciprocal translocation 5p15;11q23, segregating in 4 generations of this family. Twelve out of 16 at-risk relatives of inheriting the translocation were shown to be carriers, giving a significant (p less than .05) 3:1 ratio of carriers/noncarriers. The breakpoint on chromosome 11 at q23 is a folate sensitive fragile site into where the proto-oncogene c-ets has been mapped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There have been at least 19 cases of trisomy11q reported previously due to translocations with chromosomes other than 22: 2q37 [Lurie et al, 1979], 3p26/27 [Bader et al, 1978; Ridler and McKeown, 1979], 4q35 [Francke et al, 1977; Pihko et al, 1981], 5p15 [Mann and Rafferty, 1972; Mutchinick et al, 1988; Wallerstein et al, 1992], 6q27 [Francke et al, 1977], 8q24 [Noir et al, 1987], 9p [Greig et al, 1985], 10q26 [Tusques et al, 1972], 13p13 [Smeets et al, 1997], 13q32 [Rott et al, 1972], 17p13 [Laurent et al, 1975], 18p11 [de France et al, 1984; Menendez et al, 1990], 21q22 [Jacobsen et al, 1973], and Yq12 [Takano et al, 1993]. Each of these would result in a partial deletion of another chromosome as well as the partial trisomy 11q.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been at least 19 cases of trisomy11q reported previously due to translocations with chromosomes other than 22: 2q37 [Lurie et al, 1979], 3p26/27 [Bader et al, 1978; Ridler and McKeown, 1979], 4q35 [Francke et al, 1977; Pihko et al, 1981], 5p15 [Mann and Rafferty, 1972; Mutchinick et al, 1988; Wallerstein et al, 1992], 6q27 [Francke et al, 1977], 8q24 [Noir et al, 1987], 9p [Greig et al, 1985], 10q26 [Tusques et al, 1972], 13p13 [Smeets et al, 1997], 13q32 [Rott et al, 1972], 17p13 [Laurent et al, 1975], 18p11 [de France et al, 1984; Menendez et al, 1990], 21q22 [Jacobsen et al, 1973], and Yq12 [Takano et al, 1993]. Each of these would result in a partial deletion of another chromosome as well as the partial trisomy 11q.…”
Section: Discussionmentioning
confidence: 99%
“…The report does not document specific break point on 9p [Greig et al, 1985]. Several cases 11q trisomy have been reported with involvement of 5p [Mann and Rafferty, 1972; Mutchinick et al, 1988; Wallerstein et al, 1992]. There have been four reports of trisomy 11q that did not involve translocation with another chromosome [Forsythe et al, 1988; Pfeiffer and Schutz, 1993; de Die‐Smulders and Engelen, 1996; Delobel et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the altered cry in der(5)t(5p;11q) individuals may be independent of 11q gene dosage and is directly related to partial 5p deletion. The cry in der(5)t(5p;11q) infants has been described as either catlike (Mann and Rafferty, 1972;Mutchinick et al, 1988), high-pitched (Zhao et al, 2003), or was presumed normal (Wallerstein et al, 1992), and such phenotypic variability reflects that reported in the literature for the cry in Cri du chat syndrome (CDCS). These findings support the possi- Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Copyright © 2007 S. Karger AG, Basel A combination of segmental trisomy 11q and partial monosomy 5p arising from meiotic malsegregation of a balanced parental t(5p;11q) has only been documented in five individuals, two of whom belonged to the same family (Mann and Rafferty, 1972;Mutchinick et al, 1988;Wallerstein et al, 1992;Zhao et al, 2003). Each of these patients had a 'cat-like' or 'high-pitched' cry (Mann and Rafferty, 1972;Mutchinick et al, 1988;Zhao et al, 2003), with the exception of a female described in one sparsely detailed case (Wallerstein et al, 1992). Because no reports exist of an ab-…”
mentioning
confidence: 99%